Critical Thinking of Students in Social Studies Learning Through the Problem Basic Learning Model of Class V Students at SD Inpres 8 Mamboro - Sutriani; Nuraedah; Firmansyah , Arif (Kirana Publisher (KNPub), 2024)
Improving the quality of education in Indonesia continues to be pursued and developed along with the times. Basic education is the first stage explored by students and is the initial key for students in the stage of developing knowledge skills. Formulation of research problems How is Teacher Planning for Students' Critical Thinking in Social Studies Learning through the Problem Basic Learning Learning Model for Grade V Students at SD Inpres 8 Mamboro, How is Teacher Implementation of Students' Critical Thinking in Social Studies Learning through the Problem Basic Learning (PBL) Learning Model for Grade V Students at SD Inpres 8 Mamboro, How is Teacher Evaluation of Students' Critical Thinking in Social Studies Learning through the Problem Basic Learning (PBL) Learning Model for Grade V Students at SD Inpres 8 Mamboro, Research objectives To find out how Teacher Evaluation of Students' Critical Thinking in Social Studies Learning through the Problem Basic Learning Learning Model for Grade V Students at SD Inpres 8 Mamboro. Research methods Qualitative research is an approach to conducting research that is oriented towards natural phenomena or symptoms. Qualitative research is fundamental and naturalistic or natural in nature, and cannot be done in the laboratory, but in the field. Research Results In compiling teaching modules, teachers determine what aspects can support students in learning. The existence of planning like this makes it easy for teachers to implement according to the pattern that has been made and teachers also have guidelines in the learning process that will be carried out. So that it can direct students to think critically through teaching modules based on the problem basic learning model according to the planning that has been prepared. Conclusions in the study Realizing meaningful learning by making students think critically requires good planning. Good planning is the first step to success in learning before entering the learning implementation stage.